Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
Adasonia digitata (L.) Kuntze (commonly known as baobab) is widespread throughout the African continent, particularly in hot, dry sub-Saharan savannah environments. The tree has traditionally been used as a source of food, water and health remedies. In Southern Africa, the fruit pulp (or some- times the bark) is mixed with water and used to treat fevers, diarrhoea and haemoptysis.1,2 In Western Africa, the bark and leaves have further uses as anti- inflammatory and diaphoretic agents.3 They also have uses as traditional remedies of urinary tract infections and diarrhoea.1 This photograph was taken in the northern part of Limpopo province, South Africa by Dr Ian Cock in January 2015.